2021
DOI: 10.1371/journal.pone.0251559
|View full text |Cite
|
Sign up to set email alerts
|

English colour terms carry gender and valence biases: A corpus study using word embeddings

Abstract: In Western societies, the stereotype prevails that pink is for girls and blue is for boys. A third possible gendered colour is red. While liked by women, it represents power, stereotypically a masculine characteristic. Empirical studies confirmed such gendered connotations when testing colour-emotion associations or colour preferences in males and females. Furthermore, empirical studies demonstrated that pink is a positive colour, blue is mainly a positive colour, and red is both a positive and a negative colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 63 publications
(127 reference statements)
0
22
1
Order By: Relevance
“…Green was selected because it is one of the colors associated with male 7 , 8 and the opposite color of red in many well-established color models 41 . We did not select blue as a choice due to its prevalence as a more preferred color among both males and females 16 , 42 , as well as empirical evidence indicating its lack of gender bias 43 , 44 . Gray was chosen as an achromatic contrasting color that can be matched for saturation and lightness 45 , 46 .…”
Section: Introductionmentioning
confidence: 99%
“…Green was selected because it is one of the colors associated with male 7 , 8 and the opposite color of red in many well-established color models 41 . We did not select blue as a choice due to its prevalence as a more preferred color among both males and females 16 , 42 , as well as empirical evidence indicating its lack of gender bias 43 , 44 . Gray was chosen as an achromatic contrasting color that can be matched for saturation and lightness 45 , 46 .…”
Section: Introductionmentioning
confidence: 99%
“…Notably, limited congruency effect of green-male associations was observed. It might be related to that masculine concept was associated with blue colors more than green colors (Cunningham & Macrae, 2011;Chen et al, 2020;Jonauskaite et al, 2021). Future studies are in need to address the blue/green-male associations and testing the automaticity of those color-gender associations.…”
Section: Discussionmentioning
confidence: 97%
“…Just like word frequencies, distributional semantics can reveal biases that exist within a culture (Caliskan, Bryson, & Narayanan, 2017), or across cultures: In their analysis of 25 different languages, Lewis and Lupyan (2020) showed that people's implicit gender biases, measured in a behavioral task, are predicted by language statistics; such as, how much occupation terms like nurse and philosopher overlap with gender‐specific language in their distributional semantics ( he/she , male/female , boy/girl , man/woman , etc.). Similarly, the fact that colors have culture‐specific associations with gender in purely perceptual tasks (Jonauskaite et al., 2019) is reflected in whether color terms have semantic overlap with male‐ or female‐biased words (Jonauskaite, Sutton, Cristianini, & Mohr, 2021). Even moral beliefs are reflected in the semantics extracted from corpora (Jentzsch, Schramowski, Rothkopf, & Kersting, 2019).…”
Section: Introductionmentioning
confidence: 99%